Moisture sorption properties of matcha tea powder as affected by high humidity storage - Červenka, Libor; Palarčík, Jiří; Zeman, Vojtěch; Muriqi, Sali (University of Pardubice, 2022)
The effect of high relative humidity (RH) storage on the subsequent moisture sorption of matcha tea powder was examined. The sample of interest was stored above silicagel (control), at 52.9 and 75.3 % RH for two months at 25 °C. Moisture adsorption and desorption experiments were performed using a dynamic vapor system, and the sigmoid-shaped (type II) isotherms obtained with the aid of multi-Freundlich equation. Hysteresis loop disappeared for powder samples previously exposed to high humidity environment. According to Caurie and multi-Freundlich equations, higher critical values of aw, monolayer content, number of monolayers, and surface area of adsorption were observed for the samples stored under high RH. The change in the particle size distribution was also discussed.
Keywords: matcha tea; moisture sorption; particle size